Analysis of Environmental Awareness of Tourism Vocational Students in Central Lombok District - Muh. Zaini Hasanul Muttaqin; Agil Al Idrus; Susilawati; Muh. Makhrus; Joni Rokhmat; AA Sukarso (International Journal of Scientific Multidisciplinary Research, 2023)
The aim of this study is to analyze the level of environmental awareness of Tourism Vocational School students in Central Lombok Regency. The Central Lombok region has various tourism potentials, both natural and cultural potential. The level of environmental awareness of students greatly determines the implementation of behavior to protect the community's environment in implementing various tourism programs in Central Lombok Regency. One of the Basic Competencies of Applied Science at Tourism Vocational Schools discusses waste handling in the tourism sector. This condition places Tourism Vocational School students as one of the main actors in implementing sustainable tourism. This study was conducted using quantitative descriptive research type. The strategy used in this study is an associative strategy. The research instrument in this study used a modified questionnaire from the Waikato Regional Council research report in 2013 entitled "Environmental Awareness, Attitudes and Actions and New Ecological Paradigm Combined Survey: A survey of residents of the Waikato Region ". The respondent sampling technique used in this study was convenience sampling, by distributing questionnaires to respondents using the Google Form application. 142 respondents completed the environmental awareness questionnaire. The results of the study show that the level of environmental awareness of Tourism Vocational School students in Central Lombok Regency is categorized as low